Factors That Influence the Use of the Online Channel for the Purchase of Food Products in Spain - Alberto Luján-Salamanca; Alfonso Infante-Moro; Juan C. Infante-Moro; Julia Gallardo-Pérez (Journal of Theoretical and Applied Electronic Commerce Research)
The use of the online channel for the purchase of food products is increasing, which not only creates new opportunities for companies and businesses, but also poses great challenges. This study aimed to identify the factors related to these challenges that influence the use of the online channel for the purchase of food products in Spain. Through a bibliographic review and a Delphi study with experts, 26 factors were identified and grouped into four contexts: technology, marketing strategies, buyer convenience, and security and reliability. This identification of factors can be of great value in improving the sales of companies or businesses in the food sector that already use the online channel for the sale of their products or intend to use it for this purpose in the future; furthermore, it will help these companies or businesses to implement sales strategies that will truly satisfy the needs of potential consumers in Spain.